2021
DOI: 10.1055/s-0041-1722968
|View full text |Cite
|
Sign up to set email alerts
|

Laminectomy versus Unilateral Hemilaminectomy for the Removal of Intraspinal Schwannoma: Experience of a Single Institution and Review of Literature

Abstract: Background and Study Aims Spinal schwannomas are benign slow-growing tumors, and gross total resection is the gold standard of treatment. The conventional surgical approach is laminectomy, which provides a wide working area. Today minimally invasive surgery (MIS) is popular because it is associated with shorter hospital stay, less operative blood loss, minimized tissue traumas and relative postoperative pain, and, and spine surgery, avoidance of spinal instability. Material and Methods From January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
4
11
0
Order By: Relevance
“…22,23 Thus, hemilaminectomy has become one of the preferred surgical approaches for intradural spinal tumors and chronic degenerative diseases. 24,25 Our surgical series on lumbar spinal schwannomas also demonstrated the safety and efficacy of the hemilaminectomy approach. Our study, which is in line with a recently reported series, 24,26 showed a dramatically alleviated lower back pain and improvement in neurological function deficit at…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…22,23 Thus, hemilaminectomy has become one of the preferred surgical approaches for intradural spinal tumors and chronic degenerative diseases. 24,25 Our surgical series on lumbar spinal schwannomas also demonstrated the safety and efficacy of the hemilaminectomy approach. Our study, which is in line with a recently reported series, 24,26 showed a dramatically alleviated lower back pain and improvement in neurological function deficit at…”
Section: Discussionmentioning
confidence: 69%
“…24,25 Our surgical series on lumbar spinal schwannomas also demonstrated the safety and efficacy of the hemilaminectomy approach. Our study, which is in line with a recently reported series, 24,26 showed a dramatically alleviated lower back pain and improvement in neurological function deficit at…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Generally, the choice of surgical methods should depend on the location and extent of tumor invasion. The classic surgical approach for intradural schwannomas is the total laminectomy via posterior paramedian approach [ 18 , 19 ]. However, in recent years, this approach has been gradually replaced with the development of minimally invasive techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that unilateral laminectomy is effective in achieving complete resection of spinal tumors along with reducing the threat of postoperative deformity and spinal instability. 33,34 Re-surgery may be required in the presence of a residual tumor or tumor regrowth, and in the case of postoperative spinal instability. The present case has met the definition of a giant tumor.…”
Section: Discussionmentioning
confidence: 99%